Determination of Leptospira borgpetersenii serovar Javanica and Leptospira interrogans serovar Bataviae as the persistent Leptospira serovars circulating in the urban rat populations in Peninsular Malaysia. Issue 1 (December 2016) - Benacer, Douadi; Mohd Zain, Siti; Sim, Shin; Mohd Khalid, Mohd; Galloway, Renee; Souris, Marc; Thong, Kwai
Abstract Background Leptospirosis is an emerging infectious disease of global significance, and is endemic in tropical countries, including Malaysia. Over the last decade, a dramatic increase of human cases was reported; however, information on the primary vector, the rat, and theLeptospira serovars circulating among the rat population is limited. Therefore, the present study was undertaken to isolateLeptospira and characterise the serovars circulating in the urban rat populations from selected main cities in Peninsular Malaysia. Methods Rat trappings were carried out between October 2011 to February 2014 in five urban cities which were chosen as study sites to represent different geographical locations in Peninsular Malaysia. Microscopic agglutination test (MAT) and PCR were carried out to identify the Leptospiral serogroup and determine the pathogenic status of the isolates, respectively while pulsed-field gel electrophoresis (PFGE) and random amplified polymorphic DNA (RAPD)-PCR were used to characterize the isolates. Results Three rat species were identified from the three hundred and fifty seven rats captured withRattus rattus, being the dominant rat species (285, 80 %) followed byRattus norgevicus (53, 15 %) andRattus exulans (19, 5 %). Only 39 samples (11.0 %) were positive by culture and further confirmed as pathogenicLeptospira by PCR. Significant associations were shown between host infection with locality, season, host-age and species. Based on MAT, two serogroups were identified in the population namely;L. borgpetersenii serogroup Javanica (n = 16) andL. interrogans serogroup Bataviae (n = 23). Pulsed-field gel electrophoresis (PFGE) distinguished the two serovars in the urban rat populations:L. borgpetersenii serovar Javanica (41 %), andL. interrogans serovar Bataviae (59 %). RAPD-PCR yielded 14 distinct patterns and was found to be more discriminative than PFGE. Conclusions This study confirms twoLeptospira serovars circulating among the urban rats population in Peninsular Malaysia namely;L. borgpetersenii serovar Javanica andL. interrogans serovars Bataviae. Despite the low number of isolates obtained from the rat population, this study suggests that rodent control programs and disease surveillance may help to reduce the possible risk of disease transmission.